Identifying gene variants underlying the pathogenesis of diabetic retinopathy based on integrated genomic and transcriptomic analysis of clinical extreme phenotypes - Song, Qiaoling; Zhang, Yuchao; Zhang, Minghui; Ma, Xiaoli; Zhang, Qianyue; Zhao, Chenyang; Zhang, Zhongwen; Zhao, Huichen; Hu, Wenchao; Zhang, Xinxin; Ren, Xiwen; An, Ming; et al. (Frontiers in Genetics, 2022)
Diabetic retinopathy (DR) is a common complication and the leading cause of blindness in patients with type 2 diabetes (T2DM). DR has been shown to be closely correlated with blood glucose level and the duration of diabetes. However, the onset and progression of DR also display clinical heterogeneity. We applied whole exome sequencing and RNA-seq approaches to study the gene mutation and transcription profiles in three groups of diabetic patients with extreme clinical phenotypes in DR onset, timing, and disease progression, aiming to identify genetic variants that may play roles in the pathogenesis of DR. We identified 23 genes that were putatively pathogenic, and Ingenuity Pathway Analysis (IPA) analysis of these mutated genes reveals their functionally linking with glucose metabolism, diabetic complications, neural system activity as well as dysregulated immune responses. In addition, 10 potentially protective genes were also proposed. These findings shed light on the mechanisms underlying the pathogenesis of DR and may provide potential targets for developing new strategies to combat DR.